Phosphorus and potassium budget in the soil-plant system in crop rotations under no-till - Rosolem, Ciro Antonio [UNESP]; Calonego, Juliano Carlos [UNESP] (Elsevier, 2013)
Soil management and crop rotations can affect P and K budget in soil, decreasing losses, and increasing fertilizer use efficiency. The P and K budget in the soil-plant system at depths up to 60. cm was studied for different soil managements and crop rotations under no-till for three years in Botucatu, São Paulo, Brazil. The investigated crop rotations were: triticale (X Triticosecale) and sunflower (Helianthus annuus) cropped in autumn-winter; pearl millet (Pennisetum glaucum), forage sorghum (Sorghum bicolor), and Sunn hemp (Crotalaria juncea) were grown in the spring, as well as an additional treatment with chiseling followed by a fallow period; and soybean (Glycini max, L., Merril) was cropped in the summer. Each year triticale and sunflower were grown in plots and pearl millet, forage sorghum, Sunn hemp and of chisel/fallow in sub-plots. The triticale/millet rotation led to the largest decrease in available P within the 0-0.60. m layer of the soil profile and the largest K increase within the 0-0.05. m layer. Potassium mobility in the soil profile and the increases in the available K content in the 0.40-0.60. m layer were independent of the management system. Crop rotations with or without chiseling are not effective in preventing soil P losses. There is considerable K leaching below 0.60. m, but chiseling and the use of high K accumulating plants as triticale results in lower K losses. © 2012 Elsevier B.V.
Keywords: Cover crops; Management soil; Nutrient cycling